Central Odontogenic Fibroma: A Rare Benign Tumor With Potentially Life‐Threatening Implications - Farhad Ghorbani; Jamaledin Motazedian; Mohammad Saleh Khaghaninejad; Haleh Keshvari; Maryam Paknahad (Clinical Case Reports)
ABSTRACT Central odontogenic fibroma (COF) is a rare benign tumor originating from periodontal tissues. Although it typically grows slowly and remains asymptomatic, COF can cause significant complications when neglected, including displacement of teeth, bone destruction, and even life‐threatening airway obstruction.